Human resource management in the retail sector: challenges and trends - Kumar, Atul; Trivedi, Arpit; Dole, Vikas S.; Singh, Kiran; Yadav, Abhinav (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This article explores the challenges and trends in human resource management across the retail sector in India. The focus is on how retailers are coming to terms with wider recruitment patterns and skills sets, and how they are adapting their HR policies to suit these changes. The article also considers what this means for hiring managers in the future. Some of the challenges that Indian retailers face include finding people with experience in all of their stores; dealing with labour shortages when employees retire or become ill; attracting skilled staff, who have been displaced by automation, to work in retail; retaining staff by providing better opportunities for them to progress through training or promotion within a company; and retaining older workers so they do not leave at an age which is too early. It is argued that the retail sector has to recognize that a key function of HR is being prepared for future changes, in order to survive and flourish.